Pengaruh Pelaksanaan Kebijakan Penerimaan Siswa Baru Terhadap Manajemen Program Penerimaan Siswa Untuk Mewujudkan Efektivitas Penerimaan Siswa (Penelitian di MTs Al-Mu’awanah dan MTs Nurul Hidayatul Iman Kecamatan Singajaya) - Yusep Saepul Hayat; Ummu Salamah; Masripah Masripah (Khazanah Akademia, 2023)
The low motivation of parents to send their children to madrasas is directly related to the current issue of education there. One of the reasons for this condition is that the acceptance of new students has not gone as expected. This is because the new student admissions policy is not implemented properly and the management of the student admissions program is not managed properly. In order to maximize the effectiveness of admissions, this study examines and analyzes the impact of implementing new admissions policies on admissions program management. Census and descriptive methods are combined in this research. At MTs Al-Mu'awanah and MTs Nurul Hidayatul Iman, a sample of 51 teachers was taken from the general population. The data analysis method is a statistical path analysis model. Field studies and documentation studies are used to collect data. The value of tcount > ttable, namely = tcount 2.2190 > ttable = 2.0117 obtained from the results of hypothesis testing with path analysis. This shows that H0 is rejected and H1 is accepted. This shows that the management of the new student admissions program has a positive and significant effect on the implementation variable of the new student admissions policy in order to realize the effectiveness of student admissions. Important research findings have been revealed, so it is recommended to find a solution to this problem by following steps: 1) Arranging a student admission program earlier each academic year. This is done to adjust the program to government policies through the ministry of religion. 2) Carry out more mature planning starting from determining which students will be accepted, class targets, strategies in recruiting prospective students. 3) Gathering with community leaders, religious leaders, SD/MI heads who are targeted by madrasas by going around or by holding meetings at the madrasa.